(untitled) (Global Journal of Management and Business Research, 2018)
Large scale business organisations play a prior role in human and national development in any nation of the world. In contemporary times, this role seems not to be achieved due to internal problems of fraud, financial mismanagement, embezzlement and other crimes in management rising in these large scale business organisations. It is in consonance with the forgoing fact that this paper sought the implementation of forensic management in large scale business organisation. Forensic management is a manage-ment framework that integrates investigation approach into financial, material and human irregularities in the form of crime along side with the process of managing a particular business, establishment or organization with the aim of surfacing such irregularities, minimizing operational cost and to increase performance on the aggregate. The study begins with a brief introduction on the origin of forensic management; meaning of large scale business organisation; the framework/concept of forensic management; benefits of forensic management; phases of implementing forensic management in a business organisation; evaluating forensic management: cost and efficiency model; and strategies for effective forensic management in the large scale business organisation.